2014
DOI: 10.1016/j.psychres.2013.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors during adolescence associated with later development of psychotic disorders – A nested case-control study

Abstract: a b s t r a c tEtiologies of psychotic disorders (schizophrenia and bipolar disorder) are conceptualized as interplay between genetic and environmental factors. The adolescent period is characterized by changes in social roles and expectations that may interact with biological changes or psychosocial stressors. Few studies focus on the adolescents' own reports of perceived risk factors. To assess differences at age 16 between persons who later develop psychotic disorders ("Confirmed Psychosis", CP) and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…During 2008 and 2009 a total of 44 patients with schizophrenia spectrum disorders were coming to their first adequate treatment (i.e., not having previously received adequate antipsychotic medication in adequate doses for 12 weeks, or until remission); some had not initiated treatment at first evaluation. To enhance statistical power we additionally included 11 patients enrolled in a related study of young patients with psychosis born in 1985/86 (Bratlien et al, 2014, 2015). They were in the early phases of treatment, with an even shorter DUP than the strict first treatment patients, and met the same inclusion and exclusion criteria, except for the strict definition of first treatment.…”
Section: Methodsmentioning
confidence: 99%
“…During 2008 and 2009 a total of 44 patients with schizophrenia spectrum disorders were coming to their first adequate treatment (i.e., not having previously received adequate antipsychotic medication in adequate doses for 12 weeks, or until remission); some had not initiated treatment at first evaluation. To enhance statistical power we additionally included 11 patients enrolled in a related study of young patients with psychosis born in 1985/86 (Bratlien et al, 2014, 2015). They were in the early phases of treatment, with an even shorter DUP than the strict first treatment patients, and met the same inclusion and exclusion criteria, except for the strict definition of first treatment.…”
Section: Methodsmentioning
confidence: 99%
“…In the short time since the publication of that review, over twenty additional studies have been published, most of which provide further evidence that childhood adversities are more common among those with psychosis, again across the spectrum. Perhaps most notably, in a prospective study of 1,112 adolescents, Kelleher et al found that cessation of trauma was associated with subsequent cessation of psychotic experiences.…”
Section: Evidencementioning
confidence: 99%
“…Moreover, loneliness is associated with poorer quality of life [17] and personal recovery [18], and with more severe mental health symptoms [19]. Similarly, a number of negative health outcomes have been found to be associated with objective social isolation, for example, increased all-cause mortality rate [20], poor physical health outcomes [21,22], worse psychotic symptoms [23,24], depressive symptoms [24], and higher risk of dementia [25]. Conversely, social support that is perceived as sufficient is associated with less severe psychiatric symptoms, higher functioning, better personal recovery, greater self-esteem and empowerment, and improved quality of life [26].…”
Section: Introductionmentioning
confidence: 99%